ANALYSIS OF ELECTROMAGNETIC TRANSIENTS IN THE LOW-VOLTAGE DISTRIBUTION NETWORK OF AN INDUSTRIAL ENTERPRISE - DAVYDENKO, Liudmyla; DAVYDENKO, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Analysis of a short circuit in the distribution network with a voltage of up to 1 kV of the power supply system of an industrial enterprise. The procedure for calculating the short-circuit current in accordance with the recommendations of the ANSI/IEEE standard C37 series, which regulates the calculation of the short-circuit current for the selection and verification of switchgear and protective devices according to the short circuit current rating, was used to calculate the short-circuit current in the low-voltage distribution network of an industrial enterprise. The need to automate the process of calculating short-circuit currents in the power supply system of an industrial enterprise was substantiated. The Electrical Transient Analyzer Program (ETAP) software was used as an analysis tool. The design of the low-voltage distribution network was carried out in the ETAP software environment. The Short Circuit package of the ETAP software was used to calculate the short-circuit current on any bus of the distribution network. The result of the analysis is the determination of the short circuit current values and the verification of the compliance of the characteristics of the installed electrical equipment with the short-circuit currents. The effectiveness of using ETAP software for short-circuit analysis in order to select and verify the electrical equipment of the lowvoltage distribution network of an industrial enterprise according to the level of short-circuit current was proven. The results of the analysis of the short-circuit current using the ETAP software provided an opportunity to verify the correctness of the decisions made regarding the selection of low-voltage switchgear of the distribution network of the facility's power supply system. Analysis of short-circuit current using ETAP software provides the possibility of selecting switchgear and protective devices according to the level of short-circuit current, which contributes to the design of a reliable power supply system for the facility.
Keywords: short circuit analysis; short circuit current; maximum value of short circuit current; ETAP software